In prefrontal cortex of rat brain in an experimental schizophrenia model and the protective effects of CAPE - Ozyurt, B.; Ozyurt, H.; Atis, O.; Akpolat, N.; Akbas, A.; Sarsilmaz, M. (Wiley, 2006)
[Abstract Not Available]
31st Congress of the Federation-of-European-Biochemical-Societies (FEBS) -- JUN 24-29, 2006 -- Istanbul, TURKEY